1970
DOI: 10.1136/bmj.1.5699.773
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Illness in a General Practice. A Demographic Study and a Controlled Trial of Imipramine

Abstract: Summary: The distribution of 93 consecutive cases of depressive iliness in a Surrey general practice was found to be non-random. Married women were at risk, while men and unmarried women were largely spared. Married women were prone to the disorder at any time in their lives, and relapse was frequent. There was some suggestion that divorced wives and wives of low social class were particularly predisposed to the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…These disorders can cause considerable morbidity 2 3. Many patients with depressive disorders in primary care have a good outcome in the short term, but a significant proportion develop chronic illnesses 4 5. The treatment of depressive disorders in primary care has traditionally relied on drugs and reassurance,6 tricyclic antidepressants being more effective than placebo for patients with major depression 7 8 9 10.…”
Section: Introductionmentioning
confidence: 99%
“…These disorders can cause considerable morbidity 2 3. Many patients with depressive disorders in primary care have a good outcome in the short term, but a significant proportion develop chronic illnesses 4 5. The treatment of depressive disorders in primary care has traditionally relied on drugs and reassurance,6 tricyclic antidepressants being more effective than placebo for patients with major depression 7 8 9 10.…”
Section: Introductionmentioning
confidence: 99%
“…This author proposed that marriage created additional strain for young women which may lead to psychiatric breakdown. Porter (98) studied depression in a general practice survey, and found that while depressive illness was rare in single women, married women seemed vulnerable. This finding was not age-related, but Porter found a considerable social class difference, with the wives of non-manual workers having a lesser vulnerability, and this is in accord with the findings of Brown and his colleagues in Camberwell.…”
Section: Transition To Parenthoodmentioning
confidence: 99%
“…The results showed that both cognitive therapy and imipramine were effective, although no placebo-imipramine arm was included. One of the first placebo-controlled imipramine trials in a family doctor setting failed, however, to discriminate between active drug and placebo (Porter, 1970). On the other hand, a consequence of the Rush et al (1977) study was the gradual acceptance of imipramine for use even in patients with mild depression.…”
Section: Introductionmentioning
confidence: 99%